BS EN 3487. Aerospace series. Steel X6CrNiTi18-10 (1.4541). Air melted. Softened. Bars for machining. a or D ≤ 250 mm. 500 MPa ≤ Rm ≤ 700 MPa. (17th September 2020) - British Standards Institution
No abstract available